From keratinocyte to cancer: the pathogenesis and modeling of cutaneous squamous cell carcinoma - Ratushny, Vladimir (American Society for Clinical Investigation, 2012)
Cutaneous squamous cell carcinoma (cSCC) is the second most common human cancer with over 250,000 new cases annually in the US and is second in incidence only to basal cell carcinoma. cSCC typically manifests as a spectrum of progressively advanced malignancies, ranging from a precursor actinic keratosis (AK) to squamous cell carcinoma (SCC) in situ (SCCIS), invasive cSCC, and finally metastatic SCC. In this Review we discuss clinical and molecular parameters used to define this range of cutaneous neoplasia and integrate these with the multiple experimental approaches used to study this disease. Insights gained from modeling cSCCs have suggested innovative therapeutic targets for treating these lesions.